Italian Opera – from Failure to Success - Kozłowska, Zofia (ItaliAMO: Promotion of Italian Studies in the Academic and Non-Academic Environment, 2023)
The paper shows the history of chosen Italian opera’s masterpieces, which didn’t get recognition of the audience and of the critics in the very moment of their creation. The authoress concentrates on the circumstances of their stage exhibition, on the contemporary reactions and on their reception evolving over time.